Disseminated tumour cells from the bone marrow of early breast cancer patients: Results from an international pooled analysis. (September 2021) - Hartkopf, Andreas D.; Brucker, Sara Y.; Taran, Florin-Andrei; Harbeck, Nadia; von Au, Alexandra; Naume, Bjørn; Pierga, Jean-Yves; Hoffmann, Oliver; Beckmann, Matthias W.; Rydén, Lisa; Fehm, Tanja; Aft, Rebecca; et al.
Abstract: Purpose: Presence of disseminated tumour cells (DTCs) in the bone marrow (BM) has been described as a surrogate of residual disease in patients with early breast cancer (EBC). PADDY (Pooled Analysis of DTC Detection in Early Breast Cancer) is a large international analysis of pooled data that aimed to assess the prognostic impact of DTCs in patients with EBC. Experimental design: Individual patient data were collected from 11 centres. Patients with EBC and available follow-up data in whom BM sampling was performed at the time of primary diagnosis before receiving any anticancer treatment were eligible. DTCs were identified by antibody staining against epithelial cytokeratins. Multivariate Cox regression was used to compare the survival of DTC-positive versus DTC-negative patients. Results: In total, 10, 307 patients were included. Of these, 2814 (27.3%) were DTC-positive. DTC detection was associated with higher tumour grade, larger tumour size, nodal positivity, oestrogen receptor and progesterone receptor negativity, and HER2 positivity (all p < 0.001). Multivariate analyses showed that DTC detection was an independent prognostic marker for overall survival, disease-free survival and distant disease-free survival with hazard ratios (HR) and 95% confidence intervals (CI) of 1.23 (95% CI: 1.06–1.43, p =  0.006 ), 1.30 (95% CI: 1.12–1.52, p < 0.001) and 1.30 (95% CI: 1.08–1.56, p =  0.006 ), respectively. There was no association between locoregional relapse-free survival and DTC detection (HR 1.21; 95% CI 0.68–2.16; p =  0.512 ). Conclusions: DTCs in the BM represent an independent prognostic marker in patients with EBC. The heterogeneous metastasis-initiating potential of DTCs is consistent with the concept of cancer dormancy. Highlights: Disseminated tumour cells (DTCs) from bone marrow are detectable in breast cancer. Individual data from 11 centres were pooled, comprising a total of 10.307 patients. DTCs were detected in 27.3% of the patients and associated with impaired survival.